Apparent cohesion effects on overtopping-induced fluvial dike breaching. Issue 1 (2nd January 2021) - Rifai, Ismail; El Kadi Abderrezzak, Kamal; Hager, Willi H.; Erpicum, Sebastien; Archambeau, Pierre; Violeau, Damien; Pirotton, Michel; Dewals, Benjamin
Abstract : Flow overtopping can lead to the initiation of breaching and failure of fluvial dikes, causing severe inundations and damage in the protected areas. For flood risk management and prevention, the accurate estimate of flow discharge across the fluvial dike breach is paramount, requiring precise understanding of the breach expansion. Laboratory experiments were conducted to analyse the effects of fine sand, inducing apparent cohesion in the dike material, on breach development and outflow. Tests were conducted under controlled inflow discharge and dike material composed of either homogeneous non-cohesive coarse sand or heterogeneous fine sand/coarse sand mixtures. Based on the non-intrusive laser profilometry technique, high temporal and spatial resolution of the three-dimensional breach geometry evolution was measured, indicating a small effect of the fine material on the overall breach dynamics. A detailed analysis revealed, however, that fine sand induces less frequent slope collapses but larger sliding/failing lumps compared to homogenous non-cohesive coarse sand.